The problem of assessing endurance of hull elements of low-flying orbital objects - I. Yu. Lesnyak; Z. N. Sokolovsky; M. A. Fedorova; S. V. Gavrilenko; A. Yu. Kazakov; V. E. Konovalov (Омский научный вестник)
The paper analyzes the issue of calculating the endurance of the body of lowflying orbital objects from cyclic temperature alternating deformation beyond the limits of Hooke's law. The practical absence of direct calculation methods is stated. An indirect calculation is proposed on the basis of available experimental data on mechanical tests of samples with the «stress» parameter and an algorithm for transition from actual deformations to equivalent stresses. The calculation method is based on the use of the existing experimental fatigue curve under a symmetrical bending cycle, the results of static tensile tests at extreme cycle temperatures, and a generalization of known information about the patterns of changes in the endurance parameters of the material under consideration in relation to the conditions of cyclic temperature alternating deformation. The adequacy of the methodology is verified using the example of depressurization of the housing of the Zarya orbital module of the international space station, made of AMg6 alloy after ≈120,000 cycles of alternating temperature loading. The difference between the calculated and actual endurance of the AMg6 alloy is within the natural range of 20 % during fatigue testing.